The Insecure City Space, Power, and Mobility in Beirut - Monroe, Kristin V. (Rutgers University Press, 2016)
Urban anthropologist Kristin Monroe takes urban anthropology in a new and meaningful direction- the story of traffic in the Middle East, focusing on Beirut. As bombs reappeared recently following an impasse between competing political groups and their international backers, residents of the city were forced to contend with many forms of insecurity, forging their lives amid a contentious, often violent, political and economic landscape. Images and headlines in the news media tracked the dramatic events that characterized this unstable situation, but they did not provide a picture of what ordinary life was like for urban dwellers in a city terrorized by political sectarianism and the treat of bombs. The Insecure City is an ethnographic exploration of the experiences of moving through Beirut. Driving is characterized by precariousness, the anticipation of violence, and the constant presence of class, political, and state power. Focusing on the relationship between urban space and social class, Monroe examines how understandings and practices of spatial mobility in the city reflect social differences. Residents' access to and experiences of space are framed by uneven and insecure forms of urban citizenship. She highlights the ways in which transportation is about more than merely getting somewhere; it is also about how people encounter civic culture in a city on the edge, wounded by war. Traffic may seem to be an incidental topic for an anthropologist, but as we know in New Jersey it is central to our lives.This title was made Open Access by libraries from around the world through Knowledge Unlatched.
Description based on print version record.
Knowledge Unlatched Round 2
Keywords: Social Science; Social sciences; Electronic books